Periodontal disease related to respiratory diseases: An integrative review of the literature (Research, Society and Development, 2023)
Introduction: Periodontitis is an infectious disease that causes the destruction of periodontal ligaments and bone, and which can be a possible risk factor for several systemic diseases. One of the main causes of pneumonia in the elderly and immunocompromised is aspiration of oropharyngeal contents, and periodontitis has been epidemiologically reported as a possible risk factor for aspiration pneumonia. Objective: The aim of the work is to identify in the literature the current stage between periodontal diseases and respiratory diseases. Methodology: A survey was carried out through a systematic search in SCIELO electronic databases; VHL; LILACS. The inclusion criteria were articles published that address the relationship between periodontal disease and respiratory diseases in the last 10 years. The articles were qualified using the CONSORT table. Results: The search resulted in 99 selected articles, subject to inclusion and exclusion criteria. Thus, 38 articles were obtained, read in full, passed through several filters and qualified according to methodological quality assessment. Of the selected articles, 1 had high quality, 6 had moderate quality, 2 had low quality, 9 potentially useful articles were selected. Conclusion: It is concluded that there is a relationship between periodontal disease and respiratory diseases, however, we recommend carrying out additional studies using alternative methodologies to obtain greater clarity about this causal relationship.